Marcadores magnéticos à base de nanopartículas de ferrita recoberta com quitosana: Influência da quantidade de quitosana na morfologia e na deposição de apatita - Carvalho, Marina de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The antitumor drugs can be forwarded to their target by nanocarriers, however direct these drugs specifically to malignant cells is still difficult. However, it is assumed that the breast cancer cells have a high affinity for hydroxyapatite (main mineral phase of bone) because in its development, the occurrence of bone metastases is common. This property could be used to increase the specificity in the association of carriers with breast cancer cells. In this paper, carriers based on: magnetic nanoparticle (ferrite), coated with a biocompatible polymer, biodegradable and non-toxic (chitosan), containing on its surface particles of apatite, were developed. The influence of the proportion of ferrite / chitosan in particle morphology as well as to better anchor the procedure apatite, were evaluated in this study. It is expected that this structure allows to guide the carrier to the target with application of external magnetic field and to encapsulate the drug in the polymer portion of the nanocarrier. Furthermore it is expected that the apatite will increase the affinity of the cancer cell by the carrier. The materials were analyzed by scanning electron microscopy (MEV), infrared spectroscopy (Fourier Transform Infrared Spectroscopy, FTIR) and electrophoretic mobility measurements to determine the particle surface potential (zeta) and size distribution analysis. The proportion of ferrite/chitosan 2: 1 yielded more spherical particles. The treatment with NaOH ferrite particles coated with chitosan resulted in an increase in the amount anchored apatite. This study may contribute to the improvement of methods of diagnosis and treatment of cancer by techniques using magnetic materials as a probe and not require the use of ionizing radiation such as biosusceptometry (BAC) and magnetic hyperthermia

Os medicamentos antitumorais podem ser encaminhados a seus alvos através de nanocarreadores, entretanto direcionar esses fármacos de forma específica para células malignas é uma tarefa ainda difícil. Não obstante, presume-se que as células de câncer de mama têm uma grande afinidade pela hidroxiapatita (fase mineral principal do osso) dado que, na sua evolução, a ocorrência da metástase óssea é frequente. Essa propriedade poderia ser usada para aumentar a especificidade na associação dos carreadores com as células de câncer de mama. No presente trabalho, carreadores à base de: nanopartícula magnética (ferrita), revestida com um polímero biocompatível, biodegradável e não toxico (quitosana), contendo em sua superfície partículas de apatita, foram desenvolvidos. A influência da proporção ferrita/quitosana na morfologia da partícula, bem como procedimento para melhor ancorar a apatita foram avaliadas no presente estudo. Espera-se que esta estrutura permita guiar os carreadores até o alvo com aplicação de campo magnético externo, bem como encapsular o fármaco na porção polimérica do nanocarreador. Além disso espera-se que a apatita aumente a afinidade da célula cancerígena pelo carreador Os materiais obtidos foram analisados por microscopia eletrônica de varredura (MEV), espectroscopia no infravermelho (Fourier Transform Infrared Spectroscopy, FTIR) e medidas de mobilidade eletroforética para determinação de potencial de superfície das partículas (zeta) e análise de distribuição de tamanho. A proporção ferrita/quitosana 2:1 proporcionou partículas mais esféricas. O tratamento com NaOH das partículas de ferrita revestidas com quitosana proporcionou um aumento na quantidade ancorada de apatita. Esse estudo pode contribuir no aperfeiçoamento dos métodos de diagnose e tratamento do câncer por técnicas que utilizam materiais magnéticos como sonda e que dispensam o uso de radiação ionizante...
Keywords: Agentes antineoplasicos; Quitosana; Apatita; Nanopartículas; Ferrita; Chitosan; Apatite